(untitled) (AACINI - International Journal of Industrial Engineering, 2020)
The use of the Competency-based Approach is one of the most remarkable changes that emerge from the document Propuesta de Estándares de Segunda Generación para la Acreditación de Carreras de Ingeniería, also known as COMFEDI´s Libro Rojo. In this context, a team of teachers of the Industrial Engineering career at UNTDF began to update their study plan and teaching-learning activities. The purpose is to adapt them to the Competency-based Approach, a central requirement of the new accreditation standards. Our starting point is the definition of “Competence” by COMFEDI: “Competence is the ability of properly articulating a collection of mental structures and values, in order to provide knowledge, in a certain context, that leads to the resolution of professional issues”. In order to apply the Competency-based Model, it is necessary to confront students with the resolution of situations where they need to integrate different curricula contents. In this paper, we present an activity designed to integrate and mobilize different concepts, and a scoring rubric for its evaluation. The activity is prepared for students of the fourth year of the Industrial Engineering career, in the framework provided for the Industrial Costs curriculum unit. A summary of concepts and tools involved is also included. It is our purpose to contribute to the understanding and implementation of the Competency-based Approach in Engineering careers, through the proposal and analysis of a specific case, highlighting the difficulties to overcome and the benefits that can be obtained by applying this approach.